PENGAWASAN PENYALURAN BAHAN BAKAR MINYAK (BBM) PREMIUM DI KOTA PEKANBARU - Fitri, Aldina Nurhayatul; Tua RFS, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this research is to find out how the supervision of the distribusion of premium fuel oil (BBM) in the city of Pekanbaru and what are the inhibiting factors. This research was carried out in the Energy Resources Mineral Office Riau Province and SPBU in the Pekanbaru City. The theory used in this study is the theory of controlling by Hani Handoko, which sets the standard implementation (planning), the implementation of measuring activities, measuring the implementation of real real activities, comparing the implementation of activities with standars, and taking corrective actions if necessary. The study uses qualitative research with a descriptive approach using purposive sampling snowball sampling, and techniques obtained throught interviews, observation and documentation. The results of this study indicate that, controlling carried out by the department of Energy and Mineral Resources of Riau Province carried out has gane well but not yet maximally. Obstacle factor include human resource, budget, and controlling coordination. It isi better to increase the intensity of supervision for the welfare of the welfare of the community in meeting the needs of premium fuel.  Keywords: Controlling, Distribution, Premium Fuel (BBM)